Machado de Assis e a conspiração da posteridade : funerais cívicos, necrologias, recepção crítica (1908-1909). - Wemerson Felipe Gomes (2020)
The aim of this work is to analyze – through the necrologies and the critical-biographical reception – the constructions of memory undertaken in the circumstance of Machado de Assis's death, which occurred in September 1908. In other words, we are interested in understanding how contemporaries (and post-contemporaries consequently) “conspired” to assign the author of Dom Casmurro a prominent place in the list of the great homeland men. To a large extent, this consecratory movement responds to political, affective, and existential impulses, since remembering the deceased in a public expression of grief can be both a way to mourn (and to deal with the implications that the irreversible passing away of the loved one inevitably brings about) and an attempt to appropriate the prestige enjoyed by the deceased. In this regard, without losing sight of the affective dimension that pervades several posthumous manifestations, the necrologies (i.e., obituaries, chronicles, columns and reports that narrate the passing of the dead) will be analyzed in order to illuminate the discursive artifices mobilized in the construction and crystallization of certain images about Machado de Assis (especially those endowed with a civic connotation). On the other hand, Machado's funerals – one of the first to civically consecrate a figure in virtue of his “literary” contributions to the development of the nation – will be scrutinized aiming to exhibit some of the consecration mechanisms in vogue in the scope of the republican political culture, as well as the mishaps of the consecration process.